(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
After 40 years, the 1968 students’ movement has generated great historiographic reflection which includes testimonies, academic and political analysis, movies, and other cultural products. One of the most productive works s has been the publishing of chronics, testimony and analysis made by the same leaders of the movement. These works have been enriched by the publishing of two leaders’ testimonies: Raúl Álvarez Garín and Gilberto Guevara Niebla. Each one of them has given his version of the facts. These versions have generated coherent and complex visions which incorporate their viewpoint to a global reading of the facts. Differences and nuance are highlighted in this paper. And the most important, a first analysis on how the two leaders designed their visual strategy to support their reflections is developed.